DRY LAND AGROFORESTRY PRACTICES IN MENOREH HILLS, KULON PROGO - Aditya Hani; Yonky Indrajaya; Priyono Suryanto; Budiadi Budiadi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
Private forest in Java Island is mainly managed by Agroforestry (AF) system. There are three levels in AF systems: early AF, middle AF, and advance AF. The land productivity in AF system by villagers is mostly low because of inappropriate AF practice. The objective of this research is to analyze the land management practice in Menoreh hills, Kulon Progo, Yogyakarta. The study was conducted in Giripurwo Village, Kulon Progo. Stratifed sampling with purposive sampling was used in this study. Total of twelve plots were determined in every AF levels. Studies conducted in every plot includes the species composition and soil fertillity. The results showed that: (1) Tree composition in early and middle AF is dominated by woody tree (Sengon), while in advance AF is dominated by non-timber forest product (clove), (2) Low soil fertility in the study area is caused by high intensity of biomass harvesting and low fertilization dosage applied, (3) The increment of land productivity could be achieved by increasing the biomass input to the soil from organic fertilizer and crop waste.